Mitochondrial DNA oxidation, methylation, and copy number alterations in major and bipolar depression - Ceylan, Deniz; Karacicek, Bilge; Tufekci, Kemal Ugur; Aksahin, Izel Cemre; Senol, Sevin Hun; Genc, Sermin (Frontiers in Psychiatry, 2023)
Background Mood disorders are common disabling psychiatric disorders caused by both genetic and environmental factors. Mitochondrial DNA (mtDNA) modifications and epigenetics are promising areas of research in depression since mitochondrial dysfunction has been associated with depression. In this study we aimed to investigate the mtDNA changes in depressive disorder (MDD) and bipolar disorder (BD). Methods Displacement loop methylation (D-loop-met), relative mtDNA copy number (mtDNA-cn) and mtDNA oxidation (mtDNA-oxi) were investigated in DNA samples of individuals with MDD (n = 34), BD (n = 23), and healthy controls (HC; n = 40) using the Real-Time Polymerase Chain Reaction (RT-PCR). Blood samples were obtained from a subset of individuals with MDD (n = 15) during a depressive episode (baseline) and after remission (8th week). Results The study groups exhibited significant differences in D-loop-met (p = 0.020), while relative mtDNA-cn and mtDNA-oxi showed comparable results. During the remission phase (8th week), there were lower levels of relative mtDNA-cn (Z = −2.783, p = 0.005) and D-loop-met (Z = −3.180, p = 0.001) compared to the acute MDD baseline, with no significant change in mtDNA-oxi levels (Z = −1.193, p = 0.233). Conclusion Our findings indicate significantly increased D-loop methylation in MDD compared to BD and HCs, suggesting distinct mtDNA modifications in these conditions. Moreover, the observed alterations in relative mtDNA-cn and D-loop-met during remission suggest a potential role of mtDNA alterations in the pathophysiology of MDD. Future studies may provide valuable insights into the dynamics of mtDNA modifications in both disorders and their response to treatment.